Factors of bankruptcy among youth in Malaysia / Nurul Hidayah Nor Azmi - Nor Azmi, Nurul Hidayah (2014)
This research is study what are the factors of bankruptcy among youth in Malaysia. There are three independent variables are using in literature review which are financial management, unemployment and non-performing loan. This research also to study the relationship between three independent variables with dependent variables; factors of bankruptcy among youth in Malaysia. Researcher has used the secondary data as the research method which is by using books, journal, articles and others. At the chapter of finding and analysis, the result shows that significant or not significant between the independent variable with dependent variable.